Psychology for nurses and health profesionals - Gross, Richard D. (CRC Press/Taylor & Francis, 2014)
Psychology for Nurses and Allied Health Professionals is a practical and accessible guide providing comprehensive coverage of psychology for nurses and health care professionals in training and practice. Key features include: fully updated and restructured to ensure content matches training requirements for nurses and healthcare practitioners; stronger focus on the biopsychosocial model, therapeutic relationships and self-awareness; more practical examples to highlight application with theories demonstrated through scenarios relevant to all fields of practice; accessible style with case studies, reflection points, key points, summary boxes and glossary; free HodderPlus website with lecturer PowerPoints, extension material, MCQs and exercises. Written by the bestselling psychology author, Richard Gross, and Nancy Kinnison, a highly experienced nurse and lecturer, this is an essential guide to applying theoretical aspects of psychology to the practical aspects of nursing and health care.